2009
DOI: 10.17221/32/2008-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of some pomological traits in Minaret × Betinka apricot progeny

Abstract: ABSTRACT:In the years 2005, 2006, and 2007 the described pomological characteristics were evaluated and both heritability and correlation coefficients of the determined characteristics of parents and progeny were estimated for the Minaret × Betinka apricot hybrid population. Estimated heritability of fruit weight, over colour and flesh consistency was approximately 0.9. Heritability of flesh colour, fruit attractiveness and fruit flavour ranged from 0.6 to 0.9. The correlations show a strong dependence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 4 publications
2
11
0
Order By: Relevance
“…In terms of fruit aroma, fruit firmness, flesh colour and skin colour, the results of this study are highly consistent with those obtained by Paunovic (2000) and Krška et al (2009). The fruits of all genotypes, along with Hungarian Best, are suitable for fresh consumption.…”
Section: Analysis Of Chemical and Sensorial Fruit Traitssupporting
confidence: 87%
“…In terms of fruit aroma, fruit firmness, flesh colour and skin colour, the results of this study are highly consistent with those obtained by Paunovic (2000) and Krška et al (2009). The fruits of all genotypes, along with Hungarian Best, are suitable for fresh consumption.…”
Section: Analysis Of Chemical and Sensorial Fruit Traitssupporting
confidence: 87%
“…High heritability was assessed for all traits in both populations considering the H values, indicating a high influence of genotype on phenotypic variation. Krška et al (2009) confirmed a high H value for fruit weight over color and flesh firmness in their study.…”
Section: Broad-sense Heritability Estimates and Correlations Between supporting
confidence: 79%
“…The results of a few previous studies on inheritance of fruit quality traits in apricot indicated quantitative inheritance for most of the traits and various heritability levels for fruit quality characteristics; however, most characteristics are inherited in accordance with Mendel's laws (Krška et al, 2009).…”
Section: Variation Among Progeniesmentioning
confidence: 97%
See 2 more Smart Citations